A review of pathophysiology, mortality, risk factors and protective measures of acute kidney injury in COVID-19 patients with underlying kidney disease and kidney transplant recipients - Amirhossein Parsaei; Soroush Moradi; Hanie Karimi; Abdolkarim Haji Ghadery; Behnam Amini; Anahita Najafi; Mahnaz Momenzadeh; Leila Mostafavi; Jyoti Baharani (Society of Diabetic Nephropathy Prevention, 2022)
Acute kidney injury (AKI) is the second prevalent organ damage among COVID-19 infected individuals, which mainly affects those with critical diseases or underlying kidney disorders. Emerging data have suggested that AKI is associated with adverse outcomes, severe COVID-19 disease, and high mortality. However, the true nature and pathophysiology of COVID-19-associated kidney injury, and its effect on patients with underlying kidney diseases and transplant recipients, still remains controversial. Accordingly, this review study aimed primarily to describe the history of AKI in COVID-19 infected patients and to achieve a robust understanding of the latest findings on the mechanism of the injury. Secondly, this systematic and precise review of the literature concerning the aspects of AKI in infected patients with chronic kidney disease and transplant recipients provided a comprehensive report of mortality in these individuals. Finally, the present research suggested the possible protective measures that physicians can take to prevent, control, and treat this condition. Our study paves the way for future works with a more robust methodology to better understand COVID-19-related kidney injury